A stable demand for money despite financial crisis: The case of Venezuela - Hilde C. Bjørnland (University of Oslo, Department of Economics, 2003)
This paper investigates the demand for broad money in Venezuela, over a period of financial crisis and substantial exchange rate fluctuations. The analysis shows that there exist a long run relationship between real money, real income, inflation, the exchange rate and the domestic interest rate, that remains stable over major policy changes and large shocks. The long run properties emphasize that both inflation and exchange rate depreciations have negative effects on real money demand. The long run relationship is embedded in a dynamic equilibrium correction model with constant parameters.
Keywords: C22; C32; E41; 330; Money demand; open economy; cointegration; dynamic specifications; equilibrium correction models; Geldnachfrage; Venezuela; Finanzmarktkrise